Determination of the Cannabinoid CB1 Receptor's Positive Allosteric Modulator Binding Site through Mutagenesis Studies - Hayley M. Green; Daniel M. J. Fellner; David B. Finlay; Daniel P. Furkert; Michelle Glass (MDPI AG, 2024)
Positive allosteric modulators (PAMs) of the cannabinoid CB1 receptor (CB1) offer potential therapeutic advantages in the treatment of neuropathic pain and addiction by avoiding the adverse effects associated with orthosteric CB1 activation. Here, molecular modeling and mutagenesis were used to identify residues central to PAM activity at CB1. Six putative allosteric binding sites were identified in silico, including novel sites previously associated with cholesterol binding, and key residues within each site were mutated to alanine. The recently determined ZCZ011 binding site was found to be essential for allosteric agonism, as GAT228, GAT229 and ZCZ011 all increased wild-type G protein dissociation in the absence of an orthosteric ligand; activity that was abolished in mutants F191A3.27 and I169A2.56. PAM activity was demonstrated for ZCZ011 in the presence of the orthosteric ligand CP55940, which was only abolished in I169A2.56. In contrast, the PAM activity of GAT229 was reduced for mutants R220A3.56, L404A8.50, F191A3.27 and I169A2.56. This indicates that allosteric modulation may represent the net effect of binding at multiple sites, and that allosteric agonism is likely to be mediated via the ZCZ011 site. This study underlines the need for detailed understanding of ligand receptor interactions in the search for pure CB1 allosteric modulators.